Strategies for the Reduction of Odour Impact via Dispersion Modelling: a Case Study of a Rendering Plant - Francesca Tagliaferri; Marzio Invernizzi; Selena Sironi (Chemical Engineering Transactions, 2024)
For several years, the application of versatile Lagrangian puff models like CALPUFF has been widely acknowledged as a standard practice in numerous countries globally for forecasting odour exposure levels in the vicinity of industrial facilities. In this case study, the CALPUFF model was adopted to assess the odour impact related to a rendering plant located in Italy. For the implementation of the emission scenario, data obtained from olfactometric monitoring conducted at the plant were taken into account. The modelling study was divided into two parts. Firstly, the odour impact resulting from the current emission condition of the plant was evaluated, distinguishing between different macro-areas of the plant: production department, cooking vats, and wastewater treatment plant. Secondly, simulations of predictive impact scenarios were conducted, assuming the introduction of odour emission containment systems for the macro-areas identified as the major contributors to impact. In particular, from the simulations, it emerged that the production department contributes negligibly to the odour impacts on the surrounding area. The cooking tanks revealed odour concentrations, at the 98th percentile on an annual basis, near the closest residential areas to the plant, reaching the odour perception threshold (1 ouE/m3). The contribution of the water treatment plant proved to be significant, with concentrations estimated on some sensitive receptors around the odour nuisance threshold (5 ouE/m3). For this reason, it was hypothesized to introduce cooling systems that facilitate the condensation of vapours emitted from the cooking vats before the release into the atmosphere. In this way, based on the simulation results, receptor concentrations lower than 1 ouE/m3 would be achieved. Regarding the wastewater treatment plant, various predictive scenarios were hypothesized, assuming the covering of one or more tanks and the conveyance of air streams to be treated. The results of the different scenarios highlighted that the configuration ensuring the greatest reduction in impacts, among those analyzed, involves covering three tanks. This way, the odour impact could be reduced by approximately 80% compared to the current scenario. However, the solution that appears to be of greater interest seemed to be the closure of only one tank: in this way, by intervening on a single emission source, receptor concentrations could be reduced by an average of 60%.